Epidemiological, Clinical Features, and Complications of Scorpion Sting in the Mediterranean Region of Turkey; A Cross-sectional Study - Balcı , Erdinç; yılmaz, fevzi; Toprak, Nazmi; Zortuk, Ökkeş; Kavalcı, Cemil; Arslan, Engin deniz; Demir, Tayfun Anıl; Yavuz, Yavuz Fatih (Archives of Academic Emergency Medicine, 2026)
Introduction: Scorpion sting (SS) resulting in envenomation is a life-threatening emergency and causes serious health problems in tropical and subtropical regions. This study aimed to present the epidemiologic and clinical features of scorpion sting in the mediterranean region of Turkey. Methods: In this cross sectional study the epidemiologic, clinical characteristics, and outcomes of cases who presented to the Emergency Department (ED) of Antalya Training and Research Hospital with scorpion stings between January 2017 and December 2020 were analyzed using SPSS version 23. Results: 843 cases with the mean age of 40.49±21.26 years were evaluated (19.8% <18 years and 50.5% female). Allmost all patients (98%), had been stung by a yellow scorpion. The majority of patients were in grade 1 and grade 2 severiry (40.1%, n=338; 47.9%, n=404, respectively) according to the clinical grading. One patient died, 4.4% (n=36) were admitted to the intensive care unit and 89.4% of the patients were discharged from the ED. While cases of scorpion stings in children were prevalent during the winter months, cases affecting adults and the elderly were more common during the summer and autumn. Conclusion: The majority of scorpion stings in Antalya and its environs were with yellow scorpion, in urban area, among adults, in distal parts of the extremities, and with mild clinical severity. There was a significant correlation between age group and seasona, age group and laboratory findings, and clinical severity and laboratory findings.